Progress of urea electrocatalytic synthesis based on CO_2 and nitrite/nitrate - CHEN Hongmei; YANG Zequn; CHEN Boshi; LI Minyu; LI Hailong* (能源环境保护, 2023)
The excessive emission of CO_2 is one of the biggest environmental issues facing the 21st century, which seriously threatens the sustainable development of human society. In all kinds of ways to achieve carbon capture and transformation, converting CO_2 to high-value additional products based on electrocatalytic method is an effective way to relieve the pressure of environmental protection and industrial production, improve the utilization of carbon resources, and contribute to achieving the goal of carbon neutrality. Compared with industrial urea synthesis under high temperature and high pressure conditions, the electrocatalytic co-reduction of CO_2 and NO2-/NO3- to urea under mild conditions with low energy consumption and low secondary pollution is a promising way for industrial CO_2 utilization. From this perspective, research progress toward electrocatalytic synthesis of urea by CO_2 and NO2-/NO3- is reviewed based on the urea formation process and its intrinsic mechanism on different catalysts with the design and synthesis of catalyst and C—N coupling mechanism being highlighted. Designing materials that can co-adsorb and co-reduce CO_2 and NO2-/NO3- is a key challenge for the electrocatalytic synthesis of urea. Previous research shows that introducing defects and/or doping heteroatoms is an effective way to improve the electronic structure of the catalyst, realize the co-adsorption of CO_2 and NO_3, and improve the efficiency of urea synthesis. For the mechanisms of urea synthesis, the most reported mech⁃anism is that urea is generated by direct coupling of ∗CO and ∗NH2 intermediates or ∗COOH and ∗NH_2 intermediates. The determination of intermediates in the C—N coupling process is important in guiding the design of catalysts. The forms of key N intermediates mainly include ∗NH_2, ∗NH_2OH, ∗NH and ∗NO_2, and the key C intermediates mainly include ∗CO and ∗COOH. Besides, the future research emphasis and difficulties in related fields are further summarized and proposed based on the discussion of the catalyst design synthesis and urea formation mechanisms.